2015
DOI: 10.1111/pme.12640
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study of Chronic Pain Prevalence in the General Spanish Population: Identifying Clinical Subgroups Through Cluster Analysis

Abstract: Pain affects an important proportion of the Spanish adult population and that it has a strong personal impact. Two pain groups were clearly distinguished by their clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 37 publications
4
68
1
8
Order By: Relevance
“…Chronic pain (CP) is a health problem that has reached worldwide epidemic proportions, affecting 19%1 of the population in Europe, and between 12%1 and 16.6%2 of the adult Spanish population. Studies carried out in various countries have shown that CP is associated with the individual's quality of life, significantly limiting their activities3 4 and impeding them from maintaining an independent lifestyle 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic pain (CP) is a health problem that has reached worldwide epidemic proportions, affecting 19%1 of the population in Europe, and between 12%1 and 16.6%2 of the adult Spanish population. Studies carried out in various countries have shown that CP is associated with the individual's quality of life, significantly limiting their activities3 4 and impeding them from maintaining an independent lifestyle 1.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out in various countries have shown that CP is associated with the individual's quality of life, significantly limiting their activities3 4 and impeding them from maintaining an independent lifestyle 1. In addition, individuals suffering from CP often experience mental disturbances2 5 and their family environment may also be severely affected 6…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, algunos estudios han demostrado que el aumento de consumo de opioides está directamente relacionado con una mayor prevalencia de DC en la población (18). Este hecho también podría explicar nuestros resultados, ya que aunque no se dispone de la prevalencia de dolor crónico en estos años en el distrito sanitario objeto de estudio, es conocido que la prevalencia de dolor crónico en España ha sufrido un aumento en los últimos años pasando del 12 % en 2006 (9) al 16,6 % en 2014 (19).…”
Section: Discussionunclassified
“…El dolor crónico (DC) es un problema complejo que afecta al 16,6 % de la población general española, y en el que alrededor del 70 % de los pacientes que lo padecen están tomando algún tipo de tratamiento analgésico (8,9). Con la hipótesis de que las medidas económicas adoptadas durante el periodo de crisis podría afectar la prescripción y uso de analgésicos para tratar el dolor, en este trabajo nos propusimos como objetivo principal comparar la prescripción, el gasto y el consumo de analgésicos utilizados al inicio de la crisis económica (2008) y tras su instauración (2014), en una zona geográfica del sur-este de España, caracterizada por tener la agricultura como principal motor de su economía (10) y presentar una prevalencia de DC del 17,5 % en la población general (11).…”
Section: Introductionunclassified
“…El dolor crónico afecta más a las mujeres que a los hombres (9), planteándose que las mujeres utilizan más estrategias centradas en la emoción y los hombres más las centradas en el problema (10); pero también se afirma que utilizan más estrategias adaptativas por considerar que ejercen mayor control sobre la enfermedad (11), lo cual entraría en contradicción con el modelo básico de Lazarus y Folkman (1984), en donde se establece que la menor percepción de control se relaciona con una valoración secundaria menor (menos opciones de actuación) y mayor uso de estrategias centradas en la emoción. También hay trabajos que afirman que los hombres utilizan ante el dolor más estrategias centradas en la emoción que las mujeres (12), aunque hay estudios que indican lo contrario, observando que las mujeres utilizan más la distracción, reevaluación positiva o la religión (13), estrategias que se encuentran entre las centradas en la emoción.…”
unclassified